The SAGE Handbook of Qualitative Research - Denzin, Norman K. (Norman Kent), 1941-; Lincoln, Yvonna S. (Yvonna Sessions) (Los Angeles, CA : SAGE, 2011)
As with earlier editions, the 4th edition is virtually a new volume. The new edition continues the book's tradition of synthesizing an existing literature, defining the present, and shaping the future of qualitative research. The editors and contributors address issues of social justice and examine how people's struggles can inform public issues and in turn be transformed into social policy. Their writings are underpinned by a critical framework, and they are committed to addressing inequalities. As with previous editions, their aim is to show how the practices of qualitative research can effect change in the world in positive ways. New topics include critical social science, critical pedagogy, mixed methods, narrative inquiry, online ethnography, oral history, human rights, disability communities, queer theory, and performance ethnography.
Locating the field -- Paradigms and perspectives in contention -- Strategies of inquiry -- Methods of collecting and analyzing empirical materials -- The art and practices of interpretation, evaluation, and representation -- The future of qualitative research. -- SUMMARY: The editors and contributors address issues of social justice and examine how people's struggles can inform public issues and in turn be transformed into social policy. Their writings are underpinned by a critical framework, and they are committed to addressing issues of inequality. As with previous editions, their aim is to show how the practices of qualitative research can effect change in the world in positive ways. -- From publisher description.
1st edition: 1994.
Includes bibliographical references and indexes.
Keywords: Social sciences -- Research; Qualitative research; Social sciences; Qualitative Research; Recherche qualitative; Sciences sociales; Handbook; manuals (instructional materials); handbooks; Handbooks and manuals; Handboeken (vorm); Handbooks and manuals; Guides et manuels